Exploring the relation between clinician ratings and patient-reported experience and outcomes. (31st March 2022) - Mendlovic, Shlomo; Roe, David; Markusfeld, Geffen; Mainz, Jan; Kristensen, Solvejg; Goldzweig, Gil
Abstract: Background: Patient-reported outcome measures (PROMs) and patient-reported experience measures (PREMs) are increasingly recognized as important ways for patients to be more actively involved in their treatment and enhance shared decision-making. Objective: The current study investigated the associations between PROMs, PREMs and various symptoms measures reported by clinicians and psychiatric patients. Method: One hundred and twenty people admitted to a psychiatric hospital completed two PREMs, one PROM (the shortened version of the Manchester Short Assessment of Quality of Life scale) and Effects of Symptoms on Daily Functioning (the Sheehan Disability Scale), the Patient Clinical Global Impression and the Modified Colorado Symptom Index. Their psychiatrists rated them using the Global Assessment of Functioning scale, the Health of the Nation Outcome Scales and the Therapist Clinical Global Impression. Results: There was a strong correlation between patient's evaluation of their quality of life (PROM), experience of their care (PREM) and the overall severity of their condition and their progress. The pattern of correlation between patients' and clinicians' measures revealed a three-layer structure representing a continuum from inner experience to external presentation of experiences. Conclusion: Together these findings help identify and emphasize various domains of subjective experiences and their relation to external ratings.